Exploring Sustainable Tourism Development Strategies: A Case Study - Eri Mardiani; Adikarya, Wiwid Suryono; Ni Desak Made Santi Dwyarthi; Bucky Wibawa Karya Guna (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This research aims to explore sustainable tourism development strategies in a destination. Through in-depth case studies, this research examines various aspects related to sustainable tourism development, including environmental, social and economic aspects. This research uses a case study of one tourist destination in the coastal area. Data was collected through interviews with stakeholders, field observations, and document analysis. The research results show that implementing a sustainable tourism development strategy requires a holistic approach that pays attention to environmental sustainability, empowerment of local communities, and the creation of sustainable economic value. These findings provide valuable insights for tourism stakeholders, researchers and practitioners to design and implement more effective strategies for managing tourism in coastal destinations. This research also makes a significant contribution to the literature on sustainable tourism development by enriching understanding of the factors that influence the success of sustainable tourism development strategies in coastal destinations.